Vapor-liquid equilibria for the systems difluoromethane plus hydrogen fluoride, dichlorodifluoromethane plus hydrogen fluoride, and chlorine plus hydrogen fluoride - Kang, YW (AMER CHEMICAL SOC, 1998)
Isothermal vapor-liquid equilibria for difluoromethane + hydrogen fluoride, dichlorodifluoromethane + hydrogen fluoride, and chlorine + hydrogen fluoride have been measured. The experimental data for the binary systems are correlated with the NRTL equation with the vapor-phase association model for the mixtures containing hydrogen fluoride, and the relevant parameters are presented. The binary system difluoromethane + hydrogen fluoride forms a homogeneous liquid phase, and the others form minimum boiling heterogeneous azeotropes at the experimental conditions.
Keywords: PHASE-EQUILIBRIA; EQUATION; STATE